Glycogen synthase kinase (GSK)-3 and the double-strand RNA-dependent kinase, PKR: When two kinases for the common good turn bad (2020)
Glycogen synthase kinase (GSK)-3α/β and the double-stranded RNA-dependent kinase PKR are two sentinel kinases that carry-out multiple similar yet distinct functions in both the cytosol and the nucleus. While these kinases belong to separate signal transduction cascades, they demonstrate an uncanny propensity to regulate many of the same proteins either through direct phosphorylation or by altering transcription/translation, including: c-MYC, NF-κB, p53 and TAU, as well as each another. A significant number of studies centered on the GSK3 kinases have led to the identification of the GSK3 interactome and a number of substrates, which link GSK3 activity to metabolic control, translation, RNA splicing, ribosome biogenesis, cellular division, DNA repair and stress/inflammatory signaling. Interestingly, many of these same pathways and processes are controlled by PKR, but unlike the GSK3 kinases, a clear picture of proteins interacting with PKR and a complete listing of its substrates is still missing. In this review, we take a detailed look at what is known about the PKR and GSK3 kinases, how these kinases interact to influence common cellular processes (innate immunity, alternative splicing, translation, glucose metabolism) and how aberrant activation of these kinases leads to diseases such as Alzheimer's disease (AD), diabetes mellitus (DM) and cancer.